In Vivo Sequestration of Innate Small Molecules to Promote Bone Healing. Issue 8 (12th December 2019) - Zeng, Yuze; Shih, Yu‐Ru V.; Baht, Gurpreet S.; Varghese, Shyni
Abstract: Approaches that enable innate repair mechanisms hold great potential for tissue repair. Herein, biomaterial‐assisted sequestration of small molecules is described to localize pro‐regenerative signaling at the injury site. Specifically, a synthetic biomaterial containing boronate molecules is designed to sequester adenosine, a small molecule ubiquitously present in the human body. The biomaterial‐assisted sequestration of adenosine leverages the transient surge of extracellular adenosine following injury to prolong local adenosine signaling. It is demonstrated that implantation of the biomaterial patch following injury establishes an in situ stockpile of adenosine, resulting in accelerated healing by promoting both osteoblastogenesis and angiogenesis. The adenosine content within the patch recedes to the physiological level as the tissue regenerates. In addition to sequestering endogenous adenosine, the biomaterial is also able to deliver exogenous adenosine to the site of injury, offering a versatile solution to utilizing adenosine as a potential therapeutic for tissue repair. Abstract : A molecularly engineered biomaterial with boronate molecules sequesters endogenous adenosine. The biomaterial‐assisted sequestration leverages the transient surge of extracellular adenosine following injury to prolong local signaling, resulting in accelerated bone healing through osteoblastogenesis and angiogenesis.